Chronological changes of mumps virus genotypes in Japan between 1999–2013. Issue 7 (2nd July 2016) - Aoki, Yoko; Matoba, Yohei; Tanaka, Shizuka; Yahagi, Kazue; Itagaki, Tsutomu; Katsushima, Fumio; Katsushima, Yuriko; Takeda, Makoto; Mizuta, Katsumi
Abstract: Background : The molecular epidemiology of mumps virus (MuV) has been carried out worldwide based on genotyping proposed by the World Health Organisation. However, longitudinal molecular epidemiological studies of MuV are still limited. Methods : This study carried out genotyping of MuVs isolated in Yamagata prefecture, which is located in northern Japan, between 1999–2013, using standard nomenclature based on the sequence analysis of the entire 316 nucleotides of the small hydrophobic (SH) gene. Results : During this 15-year period, 249 MuVs were isolated, with the majority of them belonging to genotype G. Phylogenetic analysis revealed that genotype G strains were divided into two distinct clusters 1 and 2, consisting of 178 and 47 strains, respectively. The cluster 1 strains were isolated every year since 2001, except for 2012. The cluster 2 strains first appeared in 2011 and were dominant in 2011 and 2012. The epidemic pattern of genotype G strains observed in Yamagata was similar to those in Kanagawa and Hyogo prefectures located in eastern and western Japan, respectively. Only one L, three H and one F genotype strains were isolated in 2001, 2004 and 2010, respectively. Almost every year several genotype B strains related to Japanese vaccine strains were isolated. Conclusions : These data demonstrated that the genotype G strains have been endemically perpetuating as the major type over a wide area of Japan since 2001, although the genotype G strains that emerged after 2011 differed from the earlier strains.